North of Laramie - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Buck Trammel western, 2020)
"Once upon a time in the Old West, Buck Trammel was a Pinkerton agent with a promising future. But after a tragic incident in a case gone wrong, he struck out for the wide-open spaces of Wichita, Kansas. Working as a bouncer at The Gilded Lily Saloon, he hopes to stay out of trouble. But soon enough, his gun skills are put to the test. The Bowman gang shows up, turning a friendly card game with a Wyoming cattleman into a killer-takes-all shooting match. Buck saves the cattleman's life, but at the cost of Bowman's two sons. That's when Deputy Wyatt Earp arrives. He warns Buck that he'd better get out of town, pronto, and take the cattle baron with him. The rest is history--if he lives long enough to tell it . . . This is the story of Buck Trammel. Hunted by outlaws. Fighting for justice. Marked for death. This is how legends are born . . ."--Provided by publisher.